Pendidikan Tinggi di Masa dan Pasca Covid-19 - Sumantyo, Franciscus Dwikotjo Sri (Jurnal Kajian Ilmiah, 2020)
Beginning at the end of 2019 in various countries around the world and in Indonesia during the period of February 2020 has been shocked by a spectacular outbreak of a virus called Corona or Covid-19 (Corona Virus Diseases-19). This virus originally existed and developed in Wuhan China and its transmission spread very quickly throughout the world. So that the World Health Organization (WHO)(Jianxi Luo, 2020a), declared a world pandemic. Many victims fell and died, including in Indonesia and disrupt human life plus the unavailability of drugs or antidotes for this virus. All sectors in the world experience tremendous impact and ultimately jointly overcome in various ways so that transmission can be minimized, including in the field of education, especially higher education in Indonesia, many efforts have been made in the conditions and situations of teaching in the period and post-pandemic Covid-19. Government efforts in mobilizing and launching an independent campus and WFH-SFH (Nadiem Anwar Makarim, 2020a) are efforts to reduce and overcome Covid-19 servicing on campus and places of education whose potential is extraordinary, if contracting and other efforts undertaken to solve and explained in this study by each - higher education is an effort to minimize and reduce the impact caused by the Covid-19 pandemic. Keywords: Covid-19, pandemic, e-learning, independent campus, Study From Home (SFH) Abstrak Berawal akhir tahun 2019 di berbagai negara di belahan dunia dan di Indonesia dari bulan Pebruari 2020 telah dikejutkan oleh wabah spektakuler yaitu virus yang bernama Corona atau Covid-19 (Corona Virus Diseases-19). Virus ini awalnya ada dan berkembang di Wuhan China dan penularannya sangat cepat menyebar ke seluruh dunia. Sehingga oleh World Health Organization (WHO) (Jianxi Luo, 2020a), menyatakan pandemi dunia. Korban banyak berjatuhan dan meninggal dunia termasuk di Indonesia dan mengganggu kehidupan manusia ditambah belum tersedianya obat atau penangkal virus ini. Semua sektor di dunia mengalami dampak yang luar biasa dan pada akhirnya bersama-sama mengatasi dengan berbagai cara agar penularannya bisa diminimalisir, termasuk dalam bidang pendidikan, khususnya pendidikan tinggi di Indonesia telah banyak dilakukan upaya dalam kondisi dan situasi pengajaran di masa dan pasca pandemi Covid-19. Upaya pemerintah dalam menggerakkan dan mencanangkan kampus merdeka dan WFH-SFH (Nadiem Anwar Makarim, 2020a) adalah upaya untuk mengurangi dan mengatasi penyebaran Covid-19 di dalam kampus dan tempat pendidikan yang potensinya sangat luar biasa jika tertular dan upaya-upaya lain yang dilakukan untuk penanggulangannya dan dijelaskan dalam studi ini oleh masing-masing pendidikan tinggi adalah upaya dalam meminimalisir dan mengurangi dampak yang terjadi akibat pandemi Covid-19 ini. Kata Kunci: Covid-19, pandemi, pembelajaran online, kampus merdeka, belajar dari rumah